Differential Placing of Flexion Creases Contributes to Sex Differences in the Second-to-Fourth Digit Ratio (2D:4D) - Kumar, Sanjay; Voracek, Martin; Singh, Maharaj (Frontiers in Endocrinology, 2019)
The present research examined whether differential placing of the basal flexion creases contributes to the occurrence of sex differences in digit ratio (2D:4D) derived from palmar digit lengths. The ratio of palmar-to-dorsal digit length, a measure of the placing of the basal flexion crease in the finger, was derived for the digits 2 and 4 of the right hand in two independent samples (Study I: N = 100; Study II: N = 200), in accordance with discovery-replication sample approach. The results show that men have lower palmar-to-dorsal digit ratios than women, and this effect is significantly stronger for digit 2 than for digit 4. Thus, the present study supports the likelihood that differential placing of flexion creases in the digits contributes to the occurrence of sex differences in palmar 2D:4D. In addition (Study II), the measurement procedure assessing the placing of flexion creases was validated. In conclusion, this evidence highlights potential conceptual shortcomings and technical limitations in the measurement conventions and methods currently employed in the field of 2D:4D research.